PROCALCITONIN DAN INTERLEUKIN-6 PADA SEPSIS DENGAN GEJALA SYSTEMIC INFLAMMATORY RESPONSE SYNDROME (SIRS) - Indranila KS; Tjahjati DM; Emma Emma (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Sepsis is the cause of patient’s death in the intensive care unit. Sepsis is an inflammatory response to infections. Infection whencontinued can cause systemic inflammatory response syndrome (SIRS). Clinical signs and pathology of SIRS are similar to sepsis, thusclinical as well as laboratory examination is needed to distinguish these. Culture result usually can be seen at least 24 hours aftersampling. In this case a test is needed to diagnose sepsis quickly so that the patient does not experience more severe conditions. Theindicator used in the diagnostic procedure is to know the diagnostic value of procalcitonin (PCT) levels as well as of interleukin-6 (IL-6)for the diagnosis of sepsis. Thirty-two blood samples of patients treated in the Department of SIRS. Dr. Kariadi Semarang were takenconsecutively from November 2011 up to January 2012. PCT levels are determined by ELFA, levels of IL-6 were determined by ELISAmethod. To determine the sensitivity, specificity, positive predictive value and negative predictive value, 2 × 2 table was used. The ROCcurve (receiver operating characteristic) showed an area under the curve of PCT of 0.83 (95% CI = 0.66 to 0.99), cut-off 5.1 ng/mL wasused as an indicator of sepsis. PCT diagnostic test results showed 88.9% sensitivity, 73.9% specificity, 57.1% positive predictive value andnegative predictive value of 94.4%. The area under the curve for IL-6 was 0.67 (95% CI = 0.47 to 0.86), cut off 47.2 pg/mL as an indicatorof sepsis. Diagnostic tests results showed 77.8% sensitivity, 60.9% specificity, 43.7% positive predictive value and negative predictive valueof 87.5%. It can be concluded that the examination of serum PCT levels can be used as a diagnostic test (screening test) for sepsis.